Effect of spinal and epidural Analgesia on maternal and neonatal outcomes in normal vaginal deliveries - Nahid Radnia; Maryam Ataollahi; Samira Tavakolian; Nasrin Movafagh; Marziyeh Otogara; Nasrin Shirmohammadi-Khorram; Farideh Kazemi (Hamadan University of Medical Sciences, 2017)
Background. One of the main goals of medicine has been to reduce labor pain and requests from patients for pain relief is sufficient reason to use pain relief methods. This study was conducted to compare the efficacy of spinal and epidural Analgesia on maternal and neonatal outcomes. Methods. This study was a quasi-experimental clinical trial that was conducted on 126 pregnant women. Pregnant women who had inclusion criteria and informed consent were enrolled in the study and were assigned to spinal and epidural groups.  The control group were selected from among those meet inclusion criteria but were unwilling to do analgesia. Three groups were compared using statistical tests. P<0.05 was also considered significant. Results. The results showed that during the first and second stages of labor was shorter in the control group compared to spinal and epidural groups but this difference was not statistically significant. Compare the method of delivery, Apgar and episiotomy pain scores showed no statistically significant difference among the three groups. None of the participants did not develop complications such as headache and hyperthermia. Conclusion. The findings of this study showed that none of the methods of analgesia had not the negative impact on maternal and neonatal outcomes. Due to contradictory results in different studies, further studies in the same condition and with matching groups in terms of confounding variables is necessary.